A Review of Integrated Curriculum Models in Language Teaching - Amrina, Amrina; Amelia, Amelia; Nicholas, Tsai (Lingeduca: Journal of Language and Education Studies, 2024)
Integrated curriculum models in language education aim to combine multiple disciplines and language skills into a cohesive framework, fostering connections between language learning and real-world contexts. While these models offer a holistic approach, their implementation has raised concerns about effectiveness, teacher readiness, and challenges in cross-subject integration. This review evaluates the current literature on integrated curriculum models in language teaching, examining their impact on language proficiency and learner engagement. The study reviews empirical studies, case reports, and theoretical discussions, focusing on both qualitative and quantitative research that assesses outcomes in language classrooms. Key themes include cross-curricular integration, teacher collaboration, and the influence of cultural and contextual factors. Findings suggest that integrated curriculum models improve language proficiency by encouraging language use in diverse contexts, helping learners develop both language and critical thinking skills. However, successful implementation requires significant teacher collaboration and curriculum alignment. Teacher preparedness and institutional support are also crucial for achieving positive outcomes. In conclusion, integrated curriculum models hold great potential to enhance language education, but their success relies on effective implementation and collaboration between educators. Further research is needed to assess the long-term effects and scalability of these models in different educational settings.